Influence of asperities on fluid and thermal flow in a fracture: A coupled lattice Boltzmann study. Issue 7 (25th July 2013) - Neuville, A.; Flekkøy, E. G.; Toussaint, R.
<x xml:space="preserve">Abstract</x> [1] The characteristics of the hydro‐thermal flow which occurs when a cold fluid is injected into a hot fractured bedrock depend on the morphology of the fracture. We consider a sharp triangular asperity, invariant in one direction, perturbing an otherwise flat fracture. We investigate its influence on the macroscopic hydraulic transmissivity and heat transfer efficiency, at fixed low Reynolds number. In this study, numerical simulations are done with a coupled lattice Boltzmann method that solves both the complete Navier‐Stokes and advection‐diffusion equations in three dimensions. The results are compared with those obtained under lubrication approximations which rely on many hypotheses and neglect the three‐dimensional (3‐D) effects. The lubrication results are obtained by analytically solving the Stokes equation and a two‐dimensional (integrated over the thickness) advection‐diffusion equation. We use a lattice Boltzmann method with a double distribution (for mass and energy transport) on hypercubic and cubic lattices. Beyond some critical slope for the boundaries, the velocity profile is observed to be far from a quadratic profile in the vicinity of the sharp asperity: the fluid within the triangular asperity is quasi‐static. We find that taking account of both the 3‐D effects and the cooling of the rock, are important for the thermal exchange. Neglecting these effects with lubrication approximations results in overestimating the heat exchange efficiency. The evolution of the temperature over time, toward steady state, also shows complex behavior: some sites alternately reheat and cool down several times, making it difficult to forecast the extracted heat.